High intrachromosomal similarity of retrotransposon long terminal repeats: evidence for homogenization by gene conversion on plant sex chromosomes? - Kejnovsky, Eduard; Hobza, Roman; Kubat, Zdenek; Widmer, Alex; Marais, Gabriel A B; Vyskot, Boris (Gene, 2007)
Retrotransposons are ubiquitous in the plant genomes and are responsible for their plasticity. Recently, we described a novel family of gypsy-like retrotransposons, named Retand, in the dioecious plant Silene latifolia possessing evolutionary young sex chromosomes of the mammalian type (XY). Here we have analyzed long terminal repeats (LTRs) of Retand that were amplified from laser microdissected X and Y sex chromosomes and autosomes of S. latifolia. A majority of X and Y-derived LTRs formed a few separate clades in phylogenetic analysis reflecting their high intrachromosomal similarity. Moreover, the LTRs localized on the Y chromosome were less divergent than the X chromosome-derived or autosomal LTRs. These data can be explained by a homogenization process, such as gene conversion, working more intensively on the Y chromosome.
Keywords: genová konverze; sekvence nukleotidů; Silene; hybridizace in situ fluorescenční; fylogeneze; Phylogeny; molekulární evoluce; Evolution, Molecular; Models, Genetic; DNA Primers; Gene Conversion; retroelementy; chromozomy rostlin; Chromosomes, Plant; Retroelements; DNA rostlinná; DNA, Plant; modely genetické; DNA primery; In Situ Hybridization, Fluorescence; Base Sequence; Terminal Repeat Sequences; koncové repetice